Biodiversity of Avifauna in Mumbri Creek of South Konkan, Deogad Taluka, Maharashtra - Dekate HM; Baviskar RN (International Journal of Life Sciences, 2016)
The present investigation was carried out in Mumbri Creek of Sindhudurg district (Lat. 16º 21’ N. Long. 73º 25’ E). The main aim of this work is to find out the productivity of the sand creek. The mangroves consist of various types of animals. Many species of birds have disappeared all over the world due to deforestation, human interference in hilly regions, quarrying in forest and pollution. Human interference in the jungle for various purposes create disturbance in the habitat of birds, hence, neither they feed properly nor can construct their nests safely. The wetland ecosystem plays an important role in conservation of birds. Thus, the wetlands serve as treasure house for the ornithologists and interested. During high tide, the birds remain on the mangrove plants, while during low tide they come down and feed on the ground or in air on varieties of insects. The mangrove swamps provide readymade food, therefore naturally, the birds stay there and during breeding season they make their nest amongst the plants where the enemies cannot reach, provided if no human interference happens. One of the other important roles that mangrove plays is that it acts as the habitat for many species of birds. Although mangroves at first glance appears to be barren and unprotected place for any animal to live in, this is precisely the aspect that many of the bird species take the advantage as it is marshy and saline area where animals do not venture. Quietness and silence are so tangible in fully developed mangrove forests, that one can hear the puff of methane bubbles coming up from the bottom as they break the surface of water. Even water itself is silent in its streamlined flow up and down with the tides. Who is not going to stay in such calm, peaceful, vibrant, rich and academic environment? Hence the birds have an undisturbed environment at their disposal, for resting, breeding, nesting and also feeding. The avifauna includes resident, local migrant and migratory. The mangroves are very important for the birds as ample of food is available to these birds and mangroves are nesting sites for these birds. The present investigation was carried in 2015.